Macroeconomic effect and risk-taking behavior in a dual banking system - Faaza Fakhrunnas; Wulan Dari; Mustika Noor Mifrahi (Universitas Islam Indonesia, 2018)
This study aims to analyze the relationship between macroeconomic factors and risk-taking behavior in a dual banking system. Adopting a panel cointegration approach, this research posits macroeconomic factors as exogenous variables and risk-taking behavior as endogenous variables. With having 468 quarterly-observations consisting of 18 banks in Indonesia during 2010-Q4 to 2017-Q1, it finds that the risk-taking behavior of the banks has a long-term relationship with macroeconomic factors. Moreover, conventional bank has long-term relationship to macroeconomic nonetheless it results inversely to Islamic bank. In terms of bank-specified characteristics, bank size and equity to asset ratio are substantial factors for the banks’ risk mitigation.